PERANCANGAN SISTEM INFORMASI KUNJUNGAN PASIEN RAWAT JALAN PADA SAAT PANDEMI COVID-19 DI PUSKESMAS SALAM - Raden Vionita Efriana; Erix Gunawan; Edi Suharto (Media Bina Ilmiah, 2022)
Community Health Center or Puskesmas, is a health service facility that organizes public health efforts. In general, data recording and reporting of daily outpatient visits at the puskesmas is still not optimal. The purpose of this study was to design an outpatient visit information system program that was created and developed to facilitate the management of Puskesmas transaction data, and to implement the results of the design in the form of a web-based application. The method used is system design through PHP and MSQL. The results of the computerized outpatient visit information system, produce accurate data, so that the patient visit information system developed for recording patient data stored in the database is expected to be able to solve the problems that occur at UPT Puskesmas Salam.